Bibliometric Exploration of Creative Industry: Trends, Influential Authors, Research Themes, and Emerging Concepts - Oktavio, Adrie; Husriah, Husriah; Harsono, Iwan (International Journal of Business, Law, and Education, 2024)
This bibliometric analysis delves into the scholarly landscape of the creative industry, offering insights into its evolution, key contributors, predominant research themes, and emerging concepts. Through comprehensive data collection from reputable scholarly databases and systematic processing, the study identifies influential literature and conducts network analysis to visualize thematic clusters and trends. Findings reveal a dynamic and interdisciplinary field, shaped by advancements in technology, globalization, and cultural exchange. The implications of the research extend to academia, industry, and policymaking, emphasizing the importance of informed decision-making, collaborative efforts, and strategic interventions to maximize the creative industry's potential for innovation, economic growth, and societal development.